Effects of 6 weeks of complex training on athletic performance and post-activation performance enhancement effect magnitude in soccer players: a cross-sectional randomized study - Krzysztofik, Michał; Jarosz, Jakub; Urbański, Robert; Aschenbrenner, Piotr; Stastny, Petr (Biology of Sport, 2025)
This study aimed to determine the effect of complex training (CT) on post-activation performance enhancement (PAPE) effect magnitude, 5- and 30-m linear sprint, 5-0-5 change of-direction (COD), back squat (BS) and hip thrust (HT) one-repetition maximum [1RM], and jumping performance (countermovement jump [CMJ], drop jump [DJ], and broad jump [BJ]). The PAPE effect was elicited before and after each intervention by 3 BS repetitions at 90% 1RM and verified by CMJ performance. Twenty-four soccer players were randomly and equally assigned to 6 weeks of either medium (MED; [65–70%1RM]) or high-intensity (HIGH; [80–85%1RM]) CT performed twice a week. The HIGH group significantly improved their 5-m time ( p < 0.001; effect size [ES] = 1.91), 30-m time ( p = 0.001; ES = 0.66), BS 1RM ( p = 0.019; ES = 0.19) and HT 1RM ( p = 0.035; ES = 0.26), BJ length ( p = 0.012; ES = 0.62) and DJ height ( p = 0.002; ES = 0.57) from pre- to post-intervention. The MED group significantly improved their 5-m time ( p = 0.004; ES = 0.52), BS 1RM ( p = 0.019; ES = 0.36) and BJ length ( p = 0.012; ES = 0.7). Significantly shorter 5-m sprint time ( p = 0.001; ES = 1.63) and greater DJ height percentage increase ( p < 0.001; ES = 1.81) were found in the HIGH group compared to the MED group. Moreover, a significant main effect of the group, indicating a higher PAPE response in the MED group compared to the HIGH group for CMJ peak power output, was observed at both pre- and post-CT intervention ( p = 0.045; η 2 = 0.171). Six weeks of either medium or high-intensity CT could be used to enhance jumping performance, linear speed and lower-body maximum strength among soccer players. Superior improvements in acceleration and DJ might be expected after high-intensity CT than medium intensity. Medium-intensity CT can improve PAPE response.